Effect of concentration of zinc-powder in epoxy-ester based anticorrosive coatings - Raycha, Yash; Kohl, Miroslav; Kalendová, Andréa (University of Pardubice, 2023)
The present work is directed to study the effect of zinc powder concentration on anticorrosive efficiency of epoxy ester resin-based anticorrosive coatings. A high performance of zinc coating for metal protection is of vital importance depending on the concentration of zinc incorporated into coating formulation. Zinc pigment gives protection against corrosion by cathodic protection and barrier protection mechanism; however, it is necessary to keep adequate dosage of zinc. A lower dosage of zinc is insufficient to obtain sufficient cathodic protection while much higher concentration leads to the pores in the film which may influence corrosion. Therefore, this study was focused on the development of highly effective zinc coatings for excellent anticorrosion protection, as well as mechanical performance, when using standardized tests on corrosion, mechanical and chemical properties.
Keywords: anticorrosive pigment; zinc dust; corrosion; protective organic coating